Incidence, prognostic impact and clinical outcomes of renal impairment in patients with multiple myeloma: a population-based registry. Issue 3 (26th November 2019) - Courant, Maxime; Orazio, Sebastien; Monnereau, Alain; Preterre, Julie; Combe, Christian; Rigothier, Claire
Abstract: Background: Renal impairment (RI), a severe complication in multiple myeloma (MM), is considered as a poor prognostic factor. Patient survival has increased with the use of novel drugs and autologous stem-cell transplantation (ASCT). However, specific evolution of the incidence of RI in MM and its impact on prognosis remain unclear. Methods: Using a population-based registry of 1038 newly diagnosed MM in Gironde, France, we evaluated the incidence trends of RI in MM patients and assessed net survival according to factors of interest using Pohar-Perme indicator and excess mortality rate regression. We also reviewed 114 cases of MM with RI to describe their clinical outcomes. Results: In our population-based study, 24.6% of MM patients presented with RI (12.9% required haemodialysis). Median survival time was 21 months in patients with RI versus not reached at 3 years for other patients (P < 0.01). Age >73 years, RI, comorbidities and non-use of drugs or ASCT were associated with excess mortality risk. The effect of RI on excess mortality rates was maximum in the first 6 months after diagnosis. In the observational study, median follow-up time was 22.5 months; factors associated with renal response were haematologic response [odds ratio (OR) 6.81; P < 0.01] and previous chronic kidney disease (OR 0.26; P = 0.04). Factors associated with 1-year overall survival were haematological [hazard ratio (HR) 0.13; P < 0.01] and renal response (HR 0.27; P = 0.03). Conclusions: RI represents an independent negative prognostic factor in MM in the first 6 months after diagnosis. Renal recovery and haematologic response are the strongest markers associated with patient survival.